1986
DOI: 10.1111/j.1570-7458.1986.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval growth inhibition of the spiny bollworm, Earias insulana, by some steroidal secondary plant compounds

Abstract: The effect of 23 secondary plant compounds including a series of steroidal aglycones and glycosides, on larval growth and pupation of Earias insulana (Boisd.) was investigated. Larvae did not develop when fed on artificial diets containing 0.2% solamargine, solasonine, tomatine, digitonin, saponin, nomilin, lawsone or coumarin. Some growth‐retarding activity was found with diets containing 0.2% ajmalicine, capsaicin, quercetin, glycyrrhizin and glycerrhetic acid. The eight compounds highly active at 0.2% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Capsaicin (capsaicinoids) is found solely in hot peppers (Capsicum spp.) and is known to 469 deter oviposition (Cowles et al, 1989), inhibit feeding (Hori et al, 2011) and delay larval growth 470 (Weissenberg et al, 1986) in insects. Glycosylation has been linked with the detoxification of 471 capsaicin by the Lepidopteran species Helicoverpa armigera, H. zea and H. assulta, resulting in 472 capsaicin glucoside, a more water-soluble compound than its aglycone and subsequently easier to 473 excrete (Ahn et al, 2011).…”
Section: Enzymatical Characterization Of the Recombinant Ugtsmentioning
confidence: 99%
“…Capsaicin (capsaicinoids) is found solely in hot peppers (Capsicum spp.) and is known to 469 deter oviposition (Cowles et al, 1989), inhibit feeding (Hori et al, 2011) and delay larval growth 470 (Weissenberg et al, 1986) in insects. Glycosylation has been linked with the detoxification of 471 capsaicin by the Lepidopteran species Helicoverpa armigera, H. zea and H. assulta, resulting in 472 capsaicin glucoside, a more water-soluble compound than its aglycone and subsequently easier to 473 excrete (Ahn et al, 2011).…”
Section: Enzymatical Characterization Of the Recombinant Ugtsmentioning
confidence: 99%
“…There are several studies on the effects of capsaicin on insects. Capsaicin is known to deter oviposition in the onion fly Delia antiqua (Diptera: Anthomyiidae) (Cowles et al, 1989), to inhibit the feeding of a ladybird beetle Henosepilachna vigintioctomaculata (Coleoptera: Coccinellidae) (Hori et al, 2011), and to retard larval growth in the spiny bollworm Earias insulana (Lepidoptera: Noctuidae) (Weissenberg et al, 1986). Capsicum extracts have larvicidal activity to two species of mosquitoes, Anopheles stephensi and Culex quinquefasciatus (Madhumathy et al, 2007), and synergistic effects with insecticides on the green peach aphid, Myzus persicae (Edelson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Added that this acid in general increased the developmental period of insects and decreased the pupal weight. Moreover, Weissenberg et al (1986) stated that the larvae of E. insulana did not pupate when fed on diets containing 0.10% coumaric acid. At the same trends, Zhu et al (2012) showed that the sub lethal concentrations of hexaflumuron reduced the larval survival of Spodoptera littura.…”
Section: Results and Discussion Efficiency Of Tested Acids On The Eggmentioning
confidence: 99%